Human Resources Management in The Green Campus Project of Universitas Trisakti - N.R , Musholiha; M.B, Susetyarto (Konsorsium Cendekiawan Indonesia, 2023)
Universitas Trisakti strives to be a pioneer and role model for other institutions in managing a good green campus environment, by implementing all environmentally friendly elements in every aspect. One of the aspects referred to is human resources, which is the most important environmentally friendly element in a green campus environment management. The success or failure of a campus environment management depends on the human resources on the campus. The management starts from the design stage, physical construction implementation, and construction supervision or construction management, up to post-occupational management. If the human resources who will manage that green campus development really understand the concept of green buildings, of green campus areas, and of the green city of Jakarta or as known as the Jakarta smart planning, then the results of analysis managing a green campus will reach the target. All stake holders of development services who participate will be satisfied, the project will bring benefit, and then the users of the building will be happy. Therefore, the research results are the need for a lot of green building skilled personnel in handling the Green Campus Project of Universitas Trisakti.